Genome-wide Identification, Characterization, and Expression Analysis of NHX Genes in Phaseolus vulgaris L. under Salt Stress: An In Silico Approach - Edinara Maria Barbosa; Jardel de Oliveira; Tiago Benedito dos Santos; Silvia Graciele Hülse de Souza (Frontiers in Bioscience-Scholar)
Background: Climate change is among the major triggering agents of abiotic stresses (e.g., saline stress), culminating in a vulnerability of common bean production systems. In recent decades, important research has identified and characterized genes that can mitigate the adverse effects caused by salt stress; among them, the Na+/H+ antiporters (NHXs) gene stands out. The NHX genes are widely distributed in all organisms and play significant roles in osmotic regulation in plants under salt stress conditions. Genome-wide identification of NHX genes has been performed in several plant species but not in Phaseolus vulgaris L. Methods: This study aimed to identify and characterize NHX genes in P. vulgaris L. using a genome-wide analysis approach conducted in silico. The common bean genome revealed nine putative PvNHX genes, and their subcellular localization, phylogenetic relationship, cis-regulatory elements, conserved motifs identification, chromosomal location, expression patterns, and interaction networks were analyzed. Results: Promoter analysis suggested that PvNHX genes shared hormone-related elements and were light-responsive and stress-responsive. Seven PvNHX genes were under the regulation of five microRNA (miRNA) families. RNA-seq analysis revealed that most PvNHX genes were expressed in response to salt stress. Currently, the most assertive strategy to confront these adversities is to use the information generated by sequencing plants to identify candidate genes that can be introgressed to improve programs in producing resilient cultures. Conclusion: These results can provide valuable information for future studies on the functional mechanism of PvNHX genes in common beans in response to salt stress.